MANDATES AND WHEREWITHALS: THE RESEARCH-TEACHING NEXUS IN GENDER MAINSTREAMING IN THE MSU-ILIGAN INSTITUTE OF TECHNOLOGY, PHILIPPINES - SIMEON, CHANDA PEARL BARIMBAO (Universitas Muhammadiyah Yogyakarta, 2017)
The Philippines has maneuvered a capillary effect of its commitment to gender equality through various domestic legislations. Gender and Development (GAD) has thus become a matter of State policy.Pursuant to a mandated policy on gender equality, this study focuses on the experience of MSU-Iligan Institute of Technology (MSU-IIT) in mainstreaming GAD in the curriculum. The aim is to evaluate policy implementation and employs the Research and Teaching (R-T) nexus as the theoretical frame. Purposive sampling was done for respondents among the faculty and students and data were gathered through in-depth interviews and Focus Group Discussion (FGD).The College of Arts and Social Sciences (CASS) have integrated GAD in two ways - through the incorporation of a subject inÂ its programs, or as an approach to teaching through faculty initiative corroboratingÂ what Annala and Makinen (2011) referred as â€œpersonified curriculumâ€. The findings reflect the crucial nexus between the conduct of GAD researches to teaching and the subjectivity in the process, contingent as it was on the competence of the teacher.The study recommends the provision of the wherewithal for teachers through a retooling process involving trainings and the development of a common GAD module. A required GAD subject for all students is likewise recommended to ensure the delivery of a certain level of uniformity in imparting the basic minimum.